Pengaruh Pemberdayaan Keluarga terhadap Perilaku Pencegahan Komplikasi Hipertensi dengan Pendekatan Theory of Planned Behavior di Desa Baumata Utara - Welmince Paulina Nggorong; Stefania E Tefa (Universitas Malahayati, 2026)
ABSTRACT Low levels of family support are characterized by non-compliance with self-management so that blood pressure increases and is uncontrolled. The purpose of this study is to determine the effect of family empowerment on preventing hypertension complications. The research method is a quantitative descriptive research design with a Quasi Experiment approach with a Pretest and Posttest two Group Design research design of family assistance on preventing hypertension complications with the Theory of Planned Behavior approach. Pre-test and post-test behavior measurements using a questionnaire were then analyzed using the Wicoxon test. The results of the study showed that knowledge related to hypertension was almost unsure about hypertension prevention measures for 30 people (60%), then Outcome evaluations category for 30 people, Normative belief category for unsure about control belief category for unsure about 30 people (60%), in caring for family members with hypertension. In addition to family empowerment, 30 people (60%) were not sure, 27 people (57%) of families did not know about family health problems, caring for patients with hypertension for 28 people (56%), modification of the physical and psychological environment for 30 people (60%), using health facilities. Conclusion: The conclusion of this study is that the influence of family empowerment based on the theory of planned behavior can be implemented by nurses by considering personal factors, social factors, and information factors in improving the family's complication prevention behavior. Keywords: Family Empowerment, Hypertension, Theory of Planned Behavior, Behavior, Complications. ABSTRAK Rendahnya tingkat dukungan keluarga ditandai dengan ketidapatuhan terhadap manajemen diri sehingga tekanan darah menjadi meningkat serta tidak terkendali Tujuan mengetahui efektivitas pada pemberdayaan keluarga terhadap pencegahan komplikasi hipertensi. Penelitian ini menggunakan metode kuantitatif dengan pendekatan Quasi Eksperimen dengan rancangan penelitian Pretest and Posttest two Group Design pendampingan keluarga terhadap pencegahan komplikasi hipertensi dengan pendekatan Theory Of Planned Behavior. Pengukuran perilaku pre-test dan post test menggunakan kuesioner kemudian dilakukan analisis dengan uji wicoxon. Hipertensi 30 orang (60%), kemudian Outcome evaluations kategori 30 orang, Normative belief kategori tidak yakin control belief kategori tidak yakin 30 orang (60%), dalam melakukan perawatan pada anggota keluarga yang mengalami hipertensi. Selain pemberdayaan keluarga tidak yakin sebanyak 30 orang (60%), 27 orang (57%) keluarga tidak mengenal masalah kesehatan keluarga, merawat pasien yang mengalami hipertensi 28 orang (56%), modifikasi lingkungan fisik dan psikologis 30 orang (60%), menggunakan fasilitas Kesehatan. Kesimpulan dari penelitian ini yaitu pengaruh pemberdayaan keluarga dapat dilakukan oleh perawat dengan memperhatikan faktor personal, faktor sosial, faktor informasi dalam meningkatkan perilaku pencegahan komplikasi oleh keluarga. Kata Kunci: Pemberdayaan Keluarga, Hipertensi,Theory of Planned Behavior, Perilaku, Komplikasi.